An analysis of theatre utilization at Sekororo District Hospital - Ramodise, Kgaugelo Betrets (My University, 2014)
BACKGROUND – District hospitals provides level of care services that are part of the basic service package for district hospitals. Services applicable to district hospitals’ operating theatres include performance of elective and emergency surgical procedures. A study was conducted at Sekororo district hospital to evaluate the functioning of the operating theatre system. AIM: To describe the profile of patients, theatre down time and theatre throughput efficiencies at the district hospital for the period 1 April 2009 – 31 March 2011. METHODOLOGY: This was a cross sectional study based on a retrospective record review. The study setting was Sekororo District Hospital Operating Theatre. The population included records of all operations performed in the theatre during the study period. Theatre utilization was calculated as well as patient throughput to assess the internal operational efficiencies. The throughput of elective and emergency cases were compared. RESULTS: A total of 702 cases were performed during the study period. The majority of cases performed in the operating theatre were maternity cases (caesarean sections). Maternity cases accounted for 602 cases. The most common indication for caesarean sections (CS) is Cephalo-pelvic Disproportion (CPD) (49.2%). For the maternity cases, the majority were emergency cases (84.33%), and 15.67% elective cases. Theatre utilization for this period was 3% (3.6% for 2009/10 and 3.2% for 2010/11). There was a statistically significant difference (p<0.01) between the average throughput for emergency and elective cases – 25 minutes for emergency cases (confidence interval 20-35 minutes) versus 62.5 minutes for elective cases (confidence interval 38.75 – 78.75 minutes). CONCLUSION: The theatre utilization rate is extremely low for this study period. Patient throughput is much more efficient for emergency cases. Further studies are required to determine resource allocation to the operating theatre that resulted in the low theatre utilization.
Thesis (M.P.H.)--University of the Witwatersrand, Faculty of Health Sciences, 2013.
Keywords: Operating Rooms; Cesarean Section